COMPARATIVE ASSESSMENT OF ANESTHESIA METHODS FOR GYNECOLOGIC SURGERY - I. I. Khusainova (Сибирский онкологический журнал)
The purpose of the study: to improve the quality of anesthesia for gynecologic cancer surgery. materials and methods. The study included 421 patients who underwent a routine hysterectomy. The patients were divided into 3 groups with respect to analgesic method. The method of multimodal balanced analgesia was used in all cases. Group I patients additionally received epidural analgesia. Group II patients did not receive epidural analgesia (the control group). Group III patients received 600 mg of gabapentin as an adjuvant to opioid analgesia. Results. A significant difference in pain intensity within the first 72 hours after surgery between 3 groups of patients was found. Oral gabapentin as an adjunct to patient-controlled epidural analgesia provided efficient pain relief, reduction in the need for opioid analgesics in the perioperative period, as well as reduction in the incidence of postoperative nausea and vomiting after surgery.